Preparation method of wave-absorbing silicon carbide fiber with in-situ coating
By precisely controlling the crosslinking and high-temperature heat treatment of SiC fibers, an in-situ carbon-rich coating is generated, which solves the problem that SiC fiber resistivity and strength in the prior art is difficult to simultaneously improve, and achieves continuous adjustable and mechanical properties of the fiber resistivity. Excellent, suitable for the preparation of wide frequency wave absorbing composite materials.
Patent Information
- Application Number
- CN202411439080.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2025-01-07
AI Technical Summary
The existing wave absorbing SiC fiber preparation technology is difficult to achieve high resistivity and high strength at the same time, and the electromagnetic wave absorption frequency band is narrow, which cannot meet the needs of wide-frequency wave absorbing materials.
By precisely controlling the cross-linking, pyrolysis and vacuum high-temperature heat treatment processes of polymer pioneers, the resistivity and mechanical properties of SiC fibers are regulated, and an in-situ carbon-rich coating is generated to achieve continuous adjustable fiber resistivity.
The resistivity of SiC fiber is adjustable while maintaining excellent mechanical properties. It is suitable for the preparation of wide-frequency wave absorbing composite materials, and overcomes the problems that low resistivity and high strength of fibers in the prior art cannot be met at the same time.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of advanced materials, and in particular to a method for preparing a microwave-absorbing silicon carbide fiber with an in-situ coating. Background Art
[0002] With the rapid development of the information age, lightweight, high-strength, broadband absorbing materials have been widely used in the fields of microwave electronic equipment and stealth weapons and equipment. At present, absorbing materials are mainly divided into two types: coating type and structural type. Among them, the traditional coating absorbing material is to mix the absorbent and adhesive and then apply it to the target surface to form an absorbing coating, which has the problem of easy falling off and narrow absorbing frequency band. The structural / absorbing integrated materials (structural type) developed in recent years are based on advanced composite materials, avoiding the shortcomings of easy peeling, easy weight gain, and poor environmental tolerance. It can have excellent load-bearing and absorbing properties at the same time, and has broad development prospects. Among them, the absorbing continuous SiC fiber is both a reinforcement and an absorber. It is a key raw material for manufacturing high-performance absorbing composite materials with integrated structure / absorbing.
[0003] The main wave absorption mechanism of absorbing SiC fiber is to achieve wave absorption through dielectric loss. By adjusting the chemical composition and microstructure of the fiber, absorbing fibers with different dielectric losses can be obtained. The maximum electromagnetic wave absorption value and microwave absorption frequency of each absorbing material are different. If SiC fibers with different resistivities are prepared into a multilayer structure, broadband wave absorption can be achieved (T.Yamamura, T. Ichikawa, M. Shibuya, US Patent 5094907, 1992; E. Tan, Y.Kagawa, AF Dericioglu, Journal of Materials Science, 2009, 44:1172). Therefore, the prerequisite for preparing high-performance broadband structure / wave absorption integrated composite materials is to obtain a series of absorbing continuous SiC fibers with different resistivities.
[0004] At present, the most mature technology for preparing absorbing SiC fibers is based on the precursor method researched and developed by Yajima (S. Yajima, J. Hayashi and M. Omori, Chemical Letters, 1975:931). The main modification methods include surface coating, chemical doping or heat treatment to control the resistivity of the fiber, and then control the absorbing performance of the fiber. The surface coating method is to form a coating material with high conductivity on the surface of SiC fiber (E. Mouchon, Ph. Colomban, J. Mater. Sci., 1996, 31(2): 323). The chemical doping method is to introduce metal elements such as Ti and Zr into the PCS precursor to adjust the electromagnetic properties of SiC fiber. The heat treatment method is to heat the fiber at high temperature for a long time, and obtain SiC fibers with different resistivity by changing the phase composition and crystallinity of the fiber (T. Ishikawa, H.Ichikawa, Y. Imai, T. Hayase, Y. Nagata, US Patent 4507354, 1985). Currently, only Nippon Carbon and UBE Industries have achieved the industrialization of continuous SiC fiber for microwave absorption, but the specific process technology for fiber preparation has not been reported in the literature. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing a microwave-absorbing silicon carbide fiber with an in-situ coating, which can achieve continuous adjustable resistivity of SiC fiber while maintaining high fiber strength by precisely controlling the crosslinking, pyrolysis and vacuum high-temperature heat treatment process of a polymer precursor. The present invention first prepares a high-resistance SiC fiber, and then changes the chemical composition and phase composition of the fiber by high-temperature heat treatment under vacuum conditions, and simultaneously generates a carbon-rich in-situ coating on the fiber surface, thereby obtaining silicon carbide fibers with different resistivities. The process is simple and suitable for the preparation of high-performance microwave-absorbing SiC fibers.
[0006] The method for preparing a microwave-absorbing silicon carbide fiber with an in-situ coating according to the present invention comprises the following steps:
[0007] 1) Preparation of polycarbosilane PCS (A);
[0008] 2) Loading polycarbosilane PCS (A) into a spinning container, heating and melting the polycarbosilane under nitrogen protection to ensure that the melting process is stable and no oxidation reaction occurs; static degassing to remove bubbles in the molten polycarbosilane; using a spinneret to extrude the degassed molten polycarbosilane to form continuous filaments, which are then wound to form fibrils (B);
[0009] 3) placing the original fiber (B) in a blast oven and heating and cross-linking to obtain the cross-linked fiber (C), ensuring that the cross-linking reaction is complete and the fiber structure is stable;
[0010] 4) placing the cross-linked fiber (C) in a high temperature furnace and subjecting it to heat treatment in a N2 atmosphere to cause the polycarbosilane in the cross-linked fiber to undergo a pyrolysis reaction, thereby obtaining a pyrolyzed SiC fiber (D) with high resistivity;
[0011] 5) The pyrolyzed SiC fiber (D) is placed in a vacuum environment for high-temperature heat treatment to obtain SiC fibers (E) with different resistivities.
[0012] The present invention firstly utilizes a precursor conversion method to melt-spin polycarbosilane, cross-link and solidify it, and perform high-temperature pyrolysis to obtain SiC fiber with high resistivity. Then, it is subjected to high-temperature heat treatment in a vacuum environment to change the composition of the fiber and generate an in-situ carbon coating on the surface, thereby finally obtaining an absorbing SiC fiber with adjustable resistivity and excellent mechanical properties.
[0013] In step 5), the vacuum degree corresponding to the vacuum environment is 10 -1 ~10 -3 Pa; the temperature of vacuum high temperature heat treatment is 1500-1700°C, the holding time is 0.5-5min, and the preferred vacuum high temperature heat treatment time is 1-3min.
[0014] During the high temperature vacuum heat treatment process, the SiC in the high resistance SiC fiber x O y The phase decomposes, the internal composition of the fiber changes, the O content decreases, and more β-SiC phase is generated; at the same time, the SiC phase on the fiber surface decomposes to generate gas-phase Si, which escapes to form an in-situ carbon-rich coating.
[0015] By changing the temperature and holding time of high-temperature vacuum heat treatment, the fiber composition and the thickness of the in-situ carbon-rich coating on the fiber surface can be adjusted, thereby adjusting the fiber resistivity.
[0016] Through short-time heat treatment, the SiC in high-resistance SiC fiber is weakened. x O y The decomposition of the phase enables the fiber to obtain adjustable resistivity while maintaining excellent mechanical properties.
[0017] If the SiC in the high-resistance SiC fiber is subjected to long-term heat treatment, x O y Excessive decomposition of the phase will cause a serious decrease in strength and even fiber powdering. Therefore, the present invention uses high-temperature rapid heat treatment to reduce the SiC in the fiber. x O y The decomposition of the phases prevents the strength of the fiber from being significantly reduced, thus ensuring that the fiber has adjustable resistivity while also having high strength.
[0018] Compared with the existing preparation process of absorbing SiC fiber, the beneficial effects of the present invention are:
[0019] (1) First, the high-resistance fiber is prepared using the mature Yajima technology route, and then the SiC in the high-resistance fiber is heat treated at high temperature in vacuum. x O y The phase and SiC phase decompose, changing the composition of the high-resistance fiber, and forming a controllable carbon-rich layer on the fiber surface, thereby obtaining SiC fibers with different resistivities, with low technical risk;
[0020] (2) Through short-term high-temperature heat treatment, SiC x O y The decomposition of the phases is controllable, which not only ensures the strength of the fiber, but also can obtain fibers with different resistivities, thus overcoming the drawback that low resistivity and high strength of the fiber cannot be simultaneously satisfied in the prior art.
[0021] (3) By adjusting the vacuum high-temperature heat treatment temperature, holding time and atmosphere vacuum degree, the chemical composition (Si, C, O ratio) and phase composition of the SiC fiber, as well as the thickness of the low-resistivity carbon-rich layer on the fiber surface can be controlled, thereby obtaining SiC fibers with different resistivities to meet the demand for high-performance absorbing SiC fibers for broadband absorbing composite materials. DETAILED DESCRIPTION
[0022] The present invention is further described in detail below in conjunction with embodiments.
[0023] The specific steps and principles of the method described in the embodiment of the present invention are described as follows:
[0024] (1) Polycarbosilane PCS (A) was prepared by the Yajima method. The number average molecular weight measured by gel permeation chromatography (GPC) was Mn=1100-1200, and the melting point measured by a melting point instrument was 195-200°C.
[0025] (2) Polycarbosilane PCS (A) was placed in a spinning container and heated to 290-310°C under nitrogen protection to melt the precursor, and then static degassing was performed for 5 hours. After extrusion into fibers using a φ0.3 mm spinneret, the winding speed was adjusted to obtain original fibers (B) with a diameter of 10-30 μm.
[0026] (3) The raw fibers (B) are placed in a forced air oven and heated to 210-230°C at a rate of 0.5-1°C / min and kept at this temperature for 1 hour to crosslink the fibers and obtain crosslinked fibers (C).
[0027] In this process, PCS is oxidized, and the Si-H bonds are oxidized to form Si-O bonds, resulting in chemical cross-linking between different PCS molecules, turning the thermoplastic PCS into a thermosetting one, thus preventing the fibers from melting and twisting during the subsequent high-temperature heat treatment process.
[0028]
[0029] (4) The cross-linked fiber (C) is placed in a high temperature furnace and then heat treated at 900-1100°C in a N2 atmosphere to obtain pyrolyzed SiC fiber (D). The resistivity of the fiber is measured by a resistance meter and is 1×10 7 ~10×10 7 Ω.cm, the fiber has a high resistivity, so it is called high-resistance fiber. During the high-temperature heat treatment process, the following chemical reactions occur:
[0030]
[0031]
[0032] The heat treatment process causes the fiber to undergo pyrolysis and inorganicization, and the cross-linked organic fiber becomes a heat-treated ceramic fiber. At this time, the fiber contains β-SiC microcrystals, but it is mainly undecomposed amorphous SiC x O y Mutually.
[0033] (5) Placing the pyrolyzed SiC fiber (D) in a vacuum environment for high temperature heat treatment to obtain SiC fibers (E) with different resistivities. The vacuum environment corresponds to a vacuum degree of 10 -1 ~10 -3 Pa; the heat treatment temperature is 1500-1700°C, and the insulation time is 0.5-5min.
[0034] In the vacuum high temperature environment of the present invention, the SiC in the fiber is treated by short-term high temperature heat treatment. x O y Phase and SiC phase will decompose:
[0035]
[0036]
[0037] First, SiC x O yThe phase is continuously pyrolyzed at high temperature to generate solid SiC and gaseous CO and SiO. The generation of gaseous CO and SiO will change the content of Si, C, and O in the fiber, thereby adjusting the resistivity of the SiC fiber. At the same time, the decomposition of the SiC phase in the fiber under vacuum conditions will generate gaseous Si and solid C, among which the gaseous Si diffuses into the environment and dissipates, forming a carbon-rich layer on the fiber surface. The carbon-rich layer has low resistivity and can change the resistivity of the SiC fiber. Therefore, by controlling the high-temperature heat treatment conditions, the composition of the fiber can be controlled and carbon-rich layers of different thicknesses can be formed on the fiber surface, thereby regulating the resistivity of the SiC fiber and obtaining a wave-absorbing SiC fiber with continuously adjustable resistivity.
[0038] Example 1
[0039] (1) Polycarbosilane (A) was prepared by the method of Yajima (Chemical Letters, 1975:931; Chemical Letters, 1975:551). The number average molecular weight measured by gel permeation chromatography (GPC) was Mn=1190, and the melting point measured by melting point instrument was 201°C.
[0040] (2) Polycarbosilane (A) is loaded into a spinning container and heated to 305°C under nitrogen protection to melt the precursor, and then static degassing is performed for 5 hours to ensure that the bubbles in the melt are completely removed. It is extruded through a φ0.3 mm spinneret and wound at a speed of 200 m / s to obtain a precursor fiber with a diameter of 20 μm, also known as the original fiber (B).
[0041] (3) The raw fiber (B) was placed in a blast oven, heated to 225°C at a rate of 1°C / min, and kept at 225°C for 1 hour to allow the fiber to undergo a cross-linking reaction, thereby obtaining a cross-linked fiber (C). Chemical element analysis showed that the oxygen content in the fiber was 8.2% at this time.
[0042] (4) The cross-linked fiber (C) was placed in a high-temperature furnace and then kept at 1000°C for 1 h in a N2 atmosphere to obtain pyrolyzed SiC fiber (D). The resistivity of the fiber was measured by a resistance meter and was 5.14×10 7 Ω.cm.
[0043] (5) The pyrolyzed SiC fiber (D) prepared in step (4) is heated to 10 -3 Pa in a vacuum environment, the heat treatment temperature was 1500°C, and the holding time was 1 min to obtain SiC fiber (E).
[0044] Transmission electron microscopy (TEM) analysis shows that a surface carbon-rich layer with a thickness of about 10 nm is formed on the surface of the obtained SiC fiber. Mechanical property measurements show that the tensile strength of the fiber after vacuum high temperature treatment is 2.5 GPa, which is slightly lower than the tensile strength of SiC fiber that has not been treated with high temperature vacuum 2.73 GPa, but still meets the application requirements. The resistivity of the fiber measured by a resistor is 122Ω.cm, and the dielectric loss tangent of the fiber is tanδ=0.25, which is suitable as a microwave absorbing medium.
[0045] Example 2
[0046] (1) Same as step (1) of Example 1.
[0047] (2) Same as step (2) of Example 1.
[0048] (3) Same as step (3) of Example 1.
[0049] (4) Same as step (4) of Example 1.
[0050] (5) The pyrolyzed SiC fiber (D) prepared in step (4) is heated to 10 -3 The SiC fiber was obtained by high temperature heat treatment at 1700°C and holding time of 3 min in a vacuum environment of 0.03 Pa.
[0051] Transmission electron microscopy (TEM) analysis shows that a surface carbon-rich layer with a thickness of about 50 nm is formed on the surface of the obtained SiC fiber. Mechanical property measurements show that the tensile strength of the fiber after vacuum high temperature treatment is 2.1 GPa, and the fiber strength is further reduced compared with Example 1, but the strength is sufficient to meet the requirements of composite material reinforcement. The resistivity of the fiber measured by a resistor is 2.56 Ω.cm, and the resistivity is significantly reduced, which is conducive to microwave absorption; the dielectric loss tangent of the fiber is tanδ=0.76, and the higher dielectric loss tangent value indicates that the fiber has better microwave absorption performance and is suitable as a microwave absorbing medium.
[0052] Example 3
[0053] (1) Polycarbosilane (A) was prepared by the Yajima method. The number average molecular weight measured by gel permeation chromatography (GPC) was Mn=1100, and the melting point measured by a melting point instrument was 195°C.
[0054] (2) Polycarbosilane (A) was placed in a spinning container and heated to 290°C under nitrogen protection to melt the precursor, and then static degassing was performed for 5 hours. After extrusion through a 0.3 mm spinneret to form fibers, the winding speed was adjusted to obtain original fibers (B) with a diameter of 10 μm.
[0055] (3) The original fibers (B) are placed in a forced air oven and heated to 210°C at a rate of 0.5°C / min. The temperature is maintained for 1 hour to crosslink the fibers and obtain crosslinked fibers (C).
[0056] (4) The cross-linked fiber (C) was placed in a high temperature furnace and heat treated at 900°C in a N2 atmosphere to obtain pyrolyzed SiC fiber (D). The resistivity of the fiber was measured by a resistance meter and was 1×10 7 Ω·cm.
[0057] (5) Place the pyrolyzed SiC fiber (D) in a vacuum chamber at 10 -1 Pa vacuum environment, high temperature heat treatment was carried out at 1500 ° C with a holding time of 0.5 min to obtain SiC fiber (E).
[0058] Example 4
[0059] (1) Polycarbosilane PCS (A) was prepared by the Yajima method. The number average molecular weight measured by gel permeation chromatography (GPC) was Mn=1200, and the melting point measured by a melting point instrument was 200°C.
[0060] (2) Polycarbosilane (A) was placed in a spinning container and heated to 310°C under nitrogen protection to melt the precursor, and then static degassing was performed for 5 hours. After extrusion through a 0.3 mm spinneret to form fibers, the winding speed was adjusted to obtain original fibers (B) with a diameter of 30 μm.
[0061] (3) The original fiber (B) is placed in a forced air oven and heated to 230°C at a rate of 1°C / min. The temperature is kept at this temperature for 1 hour to crosslink the fibers and obtain crosslinked fibers (C).
[0062] (4) The polycarbosilane (C) was placed in a high temperature furnace and heat treated at 1100°C in a N2 atmosphere to obtain pyrolyzed SiC fiber (D). The resistivity of the fiber was measured by a resistance meter and was 10×10 7 Ω·cm.
[0063] (5) Place the pyrolyzed SiC fiber (D) in a vacuum chamber at 10 -3 Pa in a vacuum environment, a high temperature heat treatment was carried out at 1700 ° C for 5 min to obtain SiC fiber (E).
[0064] Example 5
[0065] (1) Polycarbosilane PCS (A) was prepared by the Yajima method. The number average molecular weight measured by gel permeation chromatography (GPC) was Mn=1150, and the melting point measured by a melting point instrument was 198°C.
[0066] (2) Polycarbosilane PCS (A) was placed in a spinning container and heated to 300°C under nitrogen protection to melt the precursor, and then static degassing was performed for 5 hours. After extrusion into fibers using a 0.3 mm spinneret, the winding speed was adjusted to obtain original fibers (B) with a diameter of 20 μm.
[0067] (3) The original fiber (B) is placed in a forced air oven and heated to 220°C at a rate of 0.75°C / min and kept at this temperature for 1 hour to crosslink the fibers and obtain crosslinked fibers (C).
[0068] (4) The cross-linked fiber (C) was placed in a high temperature furnace and heat treated at 1000°C in a N2 atmosphere to obtain pyrolyzed SiC fiber (D). The resistivity of the fiber was measured by a resistance meter and was 5×10 7 Ω·cm.
[0069] (5) Place the pyrolyzed SiC fiber (D) in a vacuum chamber with a degree of vacuum of 5×10 -2 Pa in a vacuum environment, a high temperature heat treatment was carried out at 1600 ° C for 3 min to obtain SiC fiber (E).
[0070] Example 6
[0071] (1) Polycarbosilane PCS (A) was prepared by the Yajima method. The number average molecular weight measured by gel permeation chromatography (GPC) was Mn=1180, and the melting point measured by a melting point instrument was 197°C.
[0072] (2) Polycarbosilane PCS (A) was placed in a spinning container and heated to 305°C under nitrogen protection to melt the precursor, and then static degassing was performed for 5 hours. After extrusion into fibers using a 0.3 mm spinneret, the winding speed was adjusted to obtain original fibers (B) with a diameter of 15 μm.
[0073] (3) The original fiber (B) is placed in a forced air oven and heated to 215°C at a rate of 0.6°C / min and kept at this temperature for 1 hour to crosslink the fibers and obtain crosslinked fibers (C).
[0074] (4) The cross-linked fiber (C) was placed in a high temperature furnace and heat treated at 950°C in a N2 atmosphere to obtain pyrolyzed SiC fiber (D). The resistivity of the fiber was measured by a resistance meter and was 2×10 7 Ω·cm.
[0075] (5) Place the pyrolyzed SiC fiber (D) in a vacuum chamber with a degree of vacuum of 2×10 -2 Pa vacuum environment, high temperature heat treatment was carried out at 1550 ° C for 2 min to obtain SiC fiber (E).
[0076] Experiments show that the silicon carbide fiber prepared by the method of the present invention has both excellent mechanical properties and adjustable electromagnetic absorption properties, and can be used as a reinforcement for composite material components in the fields of microwave electronic equipment and stealth weapon equipment.
[0077] The above embodiments are only preferred embodiments of the present invention and cannot be considered to limit the scope of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the present invention.
Claims
1. A method for preparing microwave-absorbing silicon carbide fiber with in-situ coating, characterized in that: The following steps are involved: 1) Preparation of polycarbosilane PCS; 2) Load polycarbosilane PCS into a spinning container, heat and melt the polycarbosilane under nitrogen protection to ensure that the melting process is stable and no oxidation reaction occurs; static degassing to remove bubbles in the molten polycarbosilane; extrude the degassed molten polycarbosilane through a spinneret to form continuous filaments, which are then wound to form fibrils; 3) Place the original fibers in a blast oven and heat to crosslink to obtain crosslinked fibers, ensuring that the crosslinking reaction is complete and the fiber structure is stable; 4) placing the cross-linked fibers in a high temperature furnace and subjecting them to heat treatment in a N2 atmosphere to cause the polycarbosilane in the cross-linked fibers to undergo a pyrolysis reaction to obtain pyrolytic SiC fibers with high resistivity; 5) Placing the pyrolyzed SiC fibers in a vacuum environment for vacuum high-temperature heat treatment to obtain SiC fibers with different resistivities.
2. A method for preparing microwave-absorbing silicon carbide fiber with in-situ coating as claimed in claim 1, characterized in that: Firstly, the precursor conversion method is used to melt-spin polycarbosilane, cross-link and solidify it, and then pyrolyze it at high temperature to obtain SiC fiber with high resistivity. Then, it is heat-treated at high temperature in a vacuum environment to change the composition of the fiber and generate an in-situ carbon coating on the surface. Finally, the resistivity-adjustable and excellent mechanical properties of the absorbing SiC fiber are obtained.
3. A method for preparing microwave-absorbing silicon carbide fiber with in-situ coating as claimed in claim 1, characterized in that: In step 5), the vacuum degree corresponding to the vacuum environment is 10 -1 ~10 -3 Pa; the temperature of vacuum high temperature heat treatment is 1500-1700°C, and the holding time is 0.5-5min.
4. A method for preparing microwave-absorbing silicon carbide fiber with in-situ coating as claimed in claim 3, characterized in that: During the vacuum high temperature heat treatment process, the SiC in the high resistance SiC fiber x O y The phase decomposes, the internal composition of the fiber changes, the O content decreases, and more β-SiC phase is generated; at the same time, the SiC phase on the fiber surface decomposes to generate gas-phase Si, which escapes to form an in-situ carbon-rich coating.
5. The method for preparing microwave-absorbing silicon carbide fiber with in-situ coating as claimed in claim 1, characterized in that: In step 5), the fiber composition and the thickness of the in-situ carbon-rich coating on the fiber surface are adjusted by changing the temperature and holding time of the vacuum high-temperature heat treatment, thereby adjusting the fiber resistivity.
6. A method for preparing microwave-absorbing silicon carbide fiber with in-situ coating as claimed in claim 3, characterized in that: The vacuum high temperature heat treatment lasts for 1 to 3 minutes. The short-term heat treatment weakens the SiC in the high-resistance SiC fiber. x O y The decomposition of the phase enables the fiber to obtain adjustable resistivity while maintaining excellent mechanical properties.
Citation Information
Patent Citations
Manufacturing method of continuous SiC fiber with surface coated with carbon layer
CN106087112A
Preparation method of continuous silicon carbide ceramic fiber thermistor
CN106810262A
Production of silicon carbide fiber
JP2000045130A